DAMPAK KENAIKAN HARGA BERAS TERHADAP LINGKUNGAN MASYARAKAT PADA TAHUN 2018-2023 - Ruli Aissiyah; Umi Haniatul A’la (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
. This study aims to analyze the impact of rising rice prices (independent variable) on the community environment (dependent variable) during the 2018-2023 period. The significant increase in rice prices has affected various aspects of people's lives, especially for those below the poverty line. This research uses a mixed method method by collecting interview data from the community and rice traders, as well as using secondary data tables from the Central Statistics Agency (BPS). The results showed that the increase in rice prices was caused by crop failures due to extreme weather such as El Nino, which impacted on supply scarcity and the increase in rice prices forced people to look for other food alternatives such as cassava, yams, corn and sorghum. This resulted in changes in consumption patterns that affected the family economy and public health. In addition, the government's role in setting the highest retail price policy, market intervention, and subsidies are helpful in stabilizing rice prices. The study concludes that the government can address this situation with policies such as rice imports, market operations, food aid and diversification of food sources. These community adaptation measures include the purchase of subsidized rice and the search for alternative staple foods. This study emphasizes the importance of synergy between government policies and community adaptation to maintain rice price stability and welfare.